2018
DOI: 10.2147/ndt.s176399
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ERK/CREB/BDNF pathway involved in abnormal behavior of neonatally Borna virus-infected rats

Abstract: BackgroundNeuropsychiatric disorders are devastating illnesses worldwide; however, the potential involvement of viruses in the pathophysiological mechanisms of psychiatric diseases have not been clearly elucidated. Borna disease virus (BDV) is a neurotropic, noncytopathic RNA virus.Materials and methodsIn this study, we infected neonatal rats intracranially with BDV Hu-H1 and Strain V within 24 hours of birth. Psychological phenotypes were assessed using sucrose preference test, open field test, elevated plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Previous studies demonstrated that the direct phosphorylation of Ser133 in CREB was regulated by multiple upstream pathways and proteins (62,64,65), such as the protein kinase A (PKA) (62,64), ERK1/2 (66,67), phosphoinositide 3-kinase/ protein kinase B (PI3K/AKT) (68), and CaMKII (69,70) signalling pathways. In addition, evidence has accumulated for the involvement of calcium/calmodulin and intracellular Ca 2+ in the pathophysiology of mood disorders (45,47,48), indicating that a supraspinal increase in intracellular calcium contents was involved in the modulation of mood leading to a depressant-like effect in laboratory animals (45), and blocking Ca 2+ release from intracellular stores provoked a decrease in the immobility time inducing an antidepressantlike effect (45,47,48,71).…”
Section: Effects Of Gxdsf On the Expression Levels Of Camkⅱ And Creb/...mentioning
confidence: 99%
“…Previous studies demonstrated that the direct phosphorylation of Ser133 in CREB was regulated by multiple upstream pathways and proteins (62,64,65), such as the protein kinase A (PKA) (62,64), ERK1/2 (66,67), phosphoinositide 3-kinase/ protein kinase B (PI3K/AKT) (68), and CaMKII (69,70) signalling pathways. In addition, evidence has accumulated for the involvement of calcium/calmodulin and intracellular Ca 2+ in the pathophysiology of mood disorders (45,47,48), indicating that a supraspinal increase in intracellular calcium contents was involved in the modulation of mood leading to a depressant-like effect in laboratory animals (45), and blocking Ca 2+ release from intracellular stores provoked a decrease in the immobility time inducing an antidepressantlike effect (45,47,48,71).…”
Section: Effects Of Gxdsf On the Expression Levels Of Camkⅱ And Creb/...mentioning
confidence: 99%
“…15 However, persistently infected rats will have severe hippocampal damage, and slight learning and behavioral impairments can be observed. [13][14][15][16] Our previous studies have shown that BoDV-1 infection can impair the cognitive function of rats, 17,18 but the relevant mechanisms and pathways are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Given that pinocembrin modulates the ERK–CREB–BDNF pathway in the amygdala and hippocampus, this action might play a pivotal role in anxiety‐related behavior (Figure 6). 46,72,73 Overall, the present work highlights the lack of the studies related to CAPE as well as pinocembrin on anxiety‐like behavior, despite the suggestive evidence.…”
Section: Neuropharmacological Effectsmentioning
confidence: 62%